Regio’s en grenzen van mobiele telefonie in België en in het Brussels stadsgewest - Vincent Blondel; Gautier Krings; Isabelle Thomas (Brussels Studies, 2010)
In this article, we examine the existence of regions and borders in Belgium by means of an original data set of more than 200 million mobile communications and a mathematical method which allows networks to be divided into coherent groups in a natural and automatic manner. A geography of mobile communications is thus proposed based on the relative frequency of communications as well as their average duration. In the case of the relative frequency of communications, we obtain a map of Belgium composed of 17 groups or “telephone areas” that each contain only adjacent municipalities. On this first map, the area of Brussels is the only one which runs across the linguistic border and covers the three institutional regions of the country. In the case of the average duration of communications, we obtain a group in the north and a group in the south of the country. These two groups concentrate within themselves almost 98% of telephone calls; only 2% of communications are from one group to the other. The group in the south includes the 19 municipalities of Brussels, all of the municipalities in the Walloon region as well as eight municipalities with facilities located in the Flemish region. In particular, all of the municipalities with facilities in the outskirts of Brussels (with the exception of Wemmel) are part of the group in the south of the country.